From Reparative Surgery to Regenerative Surgery: State of the Art of Porous Hydroxyapatite in Cranioplasty - Zaed, Ismail; Cardia, Andrea; Stefini, Roberto (International journal of molecular sciences, 2022)
Decompressive craniectomy is one of the most common neurosurgical procedures, usually performed after neuropathological disorders, such as traumatic brain injury (TBI), but also vascular accidents (strokes), erosive tumours, infections and other congenital abnormalities. This procedure is usually followed by the reconstruction of the cranial vault, which is also known as cranioplasty (CP). The gold-standard material for the reconstruction process is the autologous bone of the patient. However, this is not always a feasible option for all patients. Several heterologous materials have been created in the last decades to overcome such limitation. One of the most prominent materials that started to be used in CP is porous hydroxyapatite. PHA is a bioceramic material from the calcium phosphate family. It is already widely used in other medical specialties and only recently in neurosurgery. In this narrative review of the literature, we summarize the evidence on the use of PHA for cranial reconstruction, highlighting the clinical properties and limitations. We also explain how this material contributed to changing the concept of cranial reconstruction from reparative to regenerative surgery.